HORIZON HARAPAN PADA NOVEL WISANGGENI: SEBUAH TINJAUAN AWAL RESEPSI SASTRA - Jaki Yudin (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2023)
Every literary work is enjoyed by readers with a background of knowledge and experience that generates a response. This study aims to describe the reader's response to the novel. The source of data in this research is the text of a novel entitled "Wisanggeni Sang Buronan" by Seno Gumira Ajidarma. This study is a qualitative descriptive study using H.R. Jauss with content analysis method. Data analysis techniques were carried out by data reduction, data presentation and data verification until conclusions were drawn. The results of this study indicate that in the novel there is a message, there is a correlation of experiences that have been experienced by the reader, there are similarities with other works, there is a relationship between the work and real life, there is also something that is contrary to reason and there are interesting things that can be emulated from the author.